Decision Support System in Determining The Route of Delivery of Goods With The Maut and WP Methods at The Kasiyah Shop - Rozaq Rais, Nendy Akbar; Efendi, Tino Feri; Pakarti, Moch Bagoes (Institut Teknologi Bisnis AAS Indonesia, 2024)
The rapid development of information technology has encouraged many companies to switch to digital platforms, including in the retail and trade sectors. Decision Support System (DSS) is one solution that can be used to help the route selection process. An effective and efficient goods delivery process is essential to support the success of logistics operations. An effective and efficient shipping process is essential to support the success of logistics operations. However, this process is often complicated and time-consuming, especially when companies receive many orders from different locations.. To overcome this challenge, the use of a Decision Support System (DSS) can be the right solution. There are various methods that can be used in DSS to support the delivery route selection process, researchers conducted research using the MAUT (Multi-Attribute Utility Theory) and WP (Weighted Points) methods. The results of this study are expected to help improve the effectiveness and efficiency of the selection process, as well as ensure that the selected route has the necessary mileage to support the operational success of logistics companies.